ARTIFICIAL INTELLIGENCE IN PUBLIC ADMINISTRATION: GOVERNANCE, ETHICS, AND DECISION-MAKING - Endang Fatmawati (Alqaprint Jatinangor, 2025)
This study explores the transformative role of Artificial Intelligence (AI) in public administration, focusing on the dimensions of governance, ethics, and decision-making. As governments increasingly adopt AI-driven systems to enhance efficiency and transparency, critical questions arise regarding accountability, algorithmic bias, and the preservation of public trust. Using a comprehensive literature review method, this paper synthesizes findings from prior studies published in reputable international journals to examine how AI reshapes administrative processes and ethical frameworks. The analysis identifies emerging patterns in governance innovation, the ethical dilemmas of data-driven decision-making, and the evolving role of human oversight in automated environments. It further highlights the dual nature of AIas a tool for improving public service delivery and as a potential source of ethical complexity. Through comparative and thematic synthesis, this study contributes to a deeper understanding of how AI technologies influence policy formulation and institutional integrity. The paper underscores the need for adaptive governance models capable of balancing innovation with ethical responsibility in the era of intelligent public administration.